ANALYSIS OF THE INSPECTION RESULTS ON THE PRIMARY COOLING PIPE OF RSG-GAS REACTOR - Abdul Hafid (SIGMA EPSILON - Buletin Ilmiah Teknologi Keselamatan Reaktor Nuklir, 2015)
Multipurpose reactor of G.A. Siwabessy (RSG-GAS) is a research reactor with 30 MWt operated by BATAN since 1987. This reactor has obtained the permission from the regulatory body of BAPETEN to operate with the silicide fuels up to year 2025. In 2003, an ageing management of RSG-GAS was formed to evaluate the ageing process of the structures, systems, and components of the reactor. To support the ageing management, an inspection activity has been conducted to assess to the primary coolant pipe after 29 years operation. The main objective of this inspection was to determine whether a thinning of the primary pipe has occurred. The method used was the non-destructive test method with ultrasonic device to measure the thickness of pipe installed in place. The measurement was conducted two times in one year time span from 2014 to 2015. The results of measurement at three different places of the primary pipe show that the thinning has been occurred although it is very small. There are two forms of thinning that is occuring, which are the non-axisymmetric and axisymmetric. The non-axisymmetric shape thinning tends to occur in the area of the primary pipe upward of the primary pump, while the axisymmetric shape occurs at the pipe downward of the primary pump. In order to provide certainty to the thinning process at the primary pipe of RSG-GAS, re-testing should be performed routinely every 5 years.